MODERASI BERAGAMA SEBAGAI JALAN DAKWAH MAYORITAS MUSLIM PADA MINORITAS NON MUSLIM - Sugianto Sugianto; Rahmat Hidayat (INSTITUT AGAMA ISLAM NEGERI METRO, 2021)
ABSTRACT This study discusses the expression of religious moderation of the majority (Muslim) group against the minority group (non-Muslim) in Rama Puja Village, East Lampung. In addition, the purpose of this study is to produce a formulation of the ideal and appropriate expression of Religious Moderation for Islamic societies that live in plural and multicultural social conditions. This type of research is descriptive qualitative with data collection methods through interviews, participant observation and documentation. In analyzing the data, the researcher applied a qualitative descriptive analysis technique. The expected results of the research are: the expression of religious moderation of the majority group against the minority of Rama Puja Village, East Lampung, manifested in political expressions, expressions of worship and expressions of social activities. On the basis of these findings, it can be used as a role model in religion, especially the majority against minority groups.